Auto Bayar App: Software Quality Assurance at PT. XY: Aplikasi Auto Bayar: Penjaminan Mutu Perangkat Lunak di PT.XY - Prakasa, Bryan Yuditya (Procedia of Engineering and Life Science, 2024)
Software Quality Assurance (SQA) plays a crucial role in the development of applications in startups like PT XY, which focuses on auto-pay applications. Startups like Auto Serba Digital often face challenges of limited time and resources, making SQA strategic in ensuring product quality and competitiveness in the market. SQA helps startups identify, prevent, and rectify software defects, reducing the risk of failure and enhancing customer satisfaction. In the context of auto-pay applications, SQA is key in securing critical payment transactions for business success, besides ensuring compliance with applicable security standards and regulations. Effectively integrating SQA into the software development lifecycle is a critical step in ensuring high-quality products and maintaining the company's reputation in a rapidly changing market. Therefore, high-quality software development with the assistance of SQA is the key to success for innovative startups like Auto Serba Digital.